Normal anthropometric profiles but high prevalence of hypertension among the elderly in Semarang City: A descriptive cross-sectional study - Prananingrum Kinasih; Elsa Pavita; Wahyu Aulia Hasibuan (AcTion: Aceh Nutrition Journal, 2026)
The increase in the elderly population poses a challenge in the field of health because it is associated with physiological changes that can affect nutritional status and increase the risk of noncommunicable diseases. Anthropometric measurements, such as body mass index (BMI) and waist circumference (WC), are important indicators for assessing nutritional status and the risk of cardiometabolic diseases. This study aimed to describe the anthropometric profile and blood pressure of older adults in Semarang City. This study used a descriptive quantitative design with a cross-sectional approach. Data were collected in the working areas of the Pegandan and Bulu Lor Community Health Centers in Semarang City in February 2024. A sample size of 80 elderly respondents was selected using purposive sampling. The results showed that most respondents were aged 60–69 years (61.25%) and were female (72.5%). Based on anthropometric profiles, 51.2% of respondents had a normal waist circumference, and 55% were not classified as obese based on BMI. However, the prevalence of hypertension among the respondents was quite high at 68.8%. In conclusion, this study shows that most older adults in Semarang City have waist circumferences within the normal range and are not obese based on their body mass index. However, the prevalence of hypertension among respondents was relatively high.